ANÁLISE DE EVENTOS ESTRESSANTES VIVENCIADOS POR IDOSOS QUE INTERAGEM SOCIALMENTE EM BAILES - Stumm, Eniva M. F.; Berlezi, Evelise M.; Maria, Kirchner, R.; Flavio, Beienke,; Henrique, Rieth, G.; Mariza, Hildebrandt, L.; Tambara, Leite, M.; Francine, Kitzmann,; Andréia, Roncato, C. (Salão do Conhecimento, 2013)
Resumo